GDNF and miRNA-29a as biomarkers in the first episode of psychosis: uncovering associations with psychosocial factors - Szwajca, Marta; Kazek, Grzegorz; Śmierciak, Natalia; Mizera, Józef; Pomierny-Chamiolo, Lucyna; Szwajca, Krzysztof; Biesaga, Beata; Pilecki, Maciej (Frontiers in Psychiatry, 2024)
Aim. Schizophrenia involves complex interactions between biological and environmental factors, including childhood trauma, cognitive impairments, and premorbid adjustment. Predicting its severity and progression remains challenging. Biomarkers like glial cell line-derived neurotrophic factor (GDNF) and miRNA-29a may bridge biological and environmental aspects. The goal was to explore the connections between miRNAs and neural proteins and cognitive functioning, childhood trauma, and premorbid adjustment in the first episode of psychosis (FEP). Method. This study included 19 FEP patients who underwent clinical evaluation with: the Childhood Trauma Questionnaire (CTQ), the Premorbid Adjustment Scale (PAS), the Positive and Negative Syndrome Scale (PANSS), and the Montreal Cognitive Assessment Scale (MoCA). Multiplex assays for plasma proteins were conducted with Luminex xMAP technology. Additionally, miRNA levels were quantitatively determined through RNA extraction, cDNA synthesis, and RT-qPCR on a 7500 Fast Real-Time PCR System. Results. Among miRNAs, only miR-29a-3p exhibited a significant correlation with PAS-C scores (r = -0.513, p = 0.025) and cognitive improvement (r = -0.505, p = 0.033). Among the analysed proteins, only GDNF showed correlations with MoCA scores at the baseline and after 3 months (r = 0.533, p = 0.0189 and r = 0.598, p = 0.007), cognitive improvement (r = 0.511, p = 0.025), and CTQ subtests. MIF concentrations correlated with the PAS-C subscale (r = -0.5670, p = 0.011). Conclusions. GDNF and miR-29a-3p are promising as biomarkers for understanding and addressing cognitive deficits in psychosis. This study links miRNA and MIF to premorbid adjustment and reveals GDNF's unique role in connection with childhood trauma.